ONE STEP FORWARD, TWO STEPS BACK: SUCCESS AND FAILURE IN RECENT TURKISH FOREIGN POLICY - Turan, Ilter (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Turkey’s growing economy and the end of the Cold war has interjected a dynamism into Turkish foreign policy. This has meant reaching to new countries and parts of the world as well as expanding and deepening existing ties. Three motivations appear to have guided Turkish foreign policy: maintaining good relations with the traditional allies; affecting changes in the global system of governance favoring rising powers; and becoming a regional leader. During the 2004-2010 Turkey has managed good relations with allies and advanced in regional leadership. Its efforts to bring about change in global system of governance as manifest in voting against sanctions against Iran has not proven successful. The Arab spring has forced Turkey to work with its allies while the crisis in Syria and the way Turkey has become involved in the crisis has undermined Turkey’s claim to regional leadership and produced other undesirable outcomes. Turkey appears to be losing its status as a regional leader and becoming only a regional actor.